The hire of labor process of Chevron Bangladesh - Akhtar, Salamah (BRAC Business School, BRAC University, 2014)
Although the hiring process for contractor positions is thought to be handled by the HR division of a company. Chevron Bangladesh has been managing this though the Hire of Labor (HOL) process which is under the ownership of the Supply Chain Management (SCM) division of the company. The suppliers in this case, called the HOL agencies have been helping to fulfill the staff augmentation need of the company since its operation in the country. With the business expansion of the company in Bangladesh, the need has been growing ever since. As the company can only hire a certain number of regular employees in a particular business year, rest of the workforce support is being covered through the HOL process. Certainly, SCM has to work cordially with HR and the whole company in supporting the recruitment of contractors. I had the opportunity to work vel}' closely and understand the HOL process being a part of the Contract dh~sion under SCM as an intern. This report is the reflection of the new processes and learning that I got exposed to under the 4 months period of my dedication and hard work. I have started the report with the history and overview of Chevron Bangladesh, the departments in the company and moved on to the description ofthe HOL process. My role and responsibility as an intern and my contribution to the process during the internship period is also described along with the learning I received. As the main part of the report, I have pointed out some of the challenges that the company still face under the HOL process and finally recommendations on how to improve the whole process and efficiently SUppOlt the staff augmentation need of the nation's 1argest gas producing company.